War Traumatisation and Its Psychological Consequences on Women of Gulu District - Eugene, Kinyanda; Musisi, Seggane (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001), 2002)
Most of the respondents in the study had experienced at least one torture event. The commonly reported physical torture experiences included beating and kicking, forced hard labor, deprivation of food, water and medicine, and tying (Kandoya). The psychological methods of torture reported included verbal threats, killing of relatives, detention and sleeping in the bush/swamps. Among women sexual abuse was predominant with rape, attempted rape and forced marriage being common. The government army (NRA/UPDF) accounted for a quarter of all torture cases, and the rebel army LRA (Kony) for 70% of all torture cases meted out to the respondents. Torture usually took place at home affecting significantly more females than males. Psychiatric disorders diagnosed included post traumatic stress disorder, depression, alcohol abuse disorder, generalized anxiety disorder, panic anxiety disorder, agoraphobia, social phobia, somatoform disorder, and suicidal thoughts. In addition, impaired function was reported in work, family relationships, and sexual function. Six percent of the respondents had homicidal thoughts.